Fibroblast Growth Factor 2 Modulates Hippocampal Microglia Activation in a Neuroinflammation Induced Model of Depression - Tang, Ming-ming; Lin, Wen-juan; Pan, Yu-qin; Li, Ying-cong (Frontiers in Cellular Neuroscience, 2018)
Recent studies indicate that disturbed structure and function of microglia can cause depression and associated neurogenesis impairments. Our previous work has demonstrated that exogenous fibroblast growth factor 2 (FGF2) reverses the depressive-like behaviors and the impaired hippocampal neurogenesis in a neuroinflammatory model of depression. However, whether and how the antidepressant effects of FGF2 involve the modulation of microglia activation has not been elucidated. In this study, to examine the effects of FGF2 on microglia activation, exogenous FGF2 was supplemented to the lateral ventricle of rats during the neuroinflammatory state induced by central lipopolysaccharides (LPS) administrations. It was found that FGF2 infusions reversed the LPS-induced depressive-like behaviors and inhibited the hippocampal microglia activation. In LPS-treated rats, FGF2 decreased the level of pro-inflammatory cytokines including interleukin (IL)-1β, IL-6 and tumor necrosis factor (TNF)-α, increased the level of IL-10, the anti-inflammatory cytokine, and reversed the decreased expression of CX3CL1, a chemokine mainly expressed by neurons and normally keeping microglia in quiescence. Further, we examined the effects of inhibited FGF2 signaling by administration of SU5402, an FGFR inhibitor. It was found that SU5402 itself evoked depressive-like behaviors, induced microglia activation, increased production of pro-inflammatory cytokines including IL-1β, IL-6, and TNF-α, and decreased the expression of CX3CL1. Two lines of results that FGF2 signaling and FGFR inhibitor can effectively but oppositely modulate the regulation of microglia and the generation of depressive-like behavior, suggesting that microglia-regulated mechanisms may underlie the antidepressant role of FGF2. The present data provide novel insights into the understanding of mechanism of neuroinflammation-associated depression and may serve as a novel mechanism-based target for the treatment of inflammation-related depression.